2018
DOI: 10.3390/nu10101385
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fats and Chronic Noncommunicable Diseases

Abstract: The role of dietary fat has been long studied as a modifiable variable in the prevention and treatment of noncommunicable cardiometabolic disease. Once heavily promoted to the public, the low-fat diet has been demonstrated to be non-effective in preventing cardiometabolic disease, and an increasing body of literature has focused on the effects of a relatively higher-fat diet. More recent evidence suggests that a diet high in healthy fat, rich in unsaturated fatty acids, such as the Mediterranean dietary patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 98 publications
0
62
0
1
Order By: Relevance
“…Small "Daddow" kernels had lower total-SFA relative abundance, higher total-UFA relative abundance and, thus, a higher UFA:SFA ratio than large kernels ( Table 3). The differences in total-SFA and total-UFA relative abundance were less than 1% but they could confer a slight health advantage on small "Daddow" kernels because of the beneficial effects of dietary UFAs in regulating lipid levels, maintaining healthy body weight and preventing inflammation [12,13,18,70]. Total-SFA relative abundance, total-UFA relative abundance and UFA:SFA ratio did not differ significantly between small and large kernels of "816" or "A4" (Table 3).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small "Daddow" kernels had lower total-SFA relative abundance, higher total-UFA relative abundance and, thus, a higher UFA:SFA ratio than large kernels ( Table 3). The differences in total-SFA and total-UFA relative abundance were less than 1% but they could confer a slight health advantage on small "Daddow" kernels because of the beneficial effects of dietary UFAs in regulating lipid levels, maintaining healthy body weight and preventing inflammation [12,13,18,70]. Total-SFA relative abundance, total-UFA relative abundance and UFA:SFA ratio did not differ significantly between small and large kernels of "816" or "A4" (Table 3).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Total-SFA relative abundance, total-UFA relative abundance and UFA:SFA ratio did not differ significantly between small and large kernels of "816" or "A4" (Table 3). However, partial replacement of one SFA, palmitic acid, with another SFA, stearic acid, in the small kernels of "816" and "A4" ( Table 2) might provide a slight health advantage because palmitic acid increases LDL-cholesterol levels whereas stearic acid does not [13,71].…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a low-fat diet has been long favored in the prevention and treatment of CVD, a diet high in unsaturated fatty acids (UFA) may hold far more cardioprotective benefit [119]. A cross-sectional analysis of 23 subjects with HFpEF and obesity demonstrated that consumption of mono-and polyunsaturated fatty acids (MUFA and PUFA, respectively) was positively correlated with relative peak VO 2 [88].…”
Section: Unsaturated Fatty Acid Supplementation In Hfpefmentioning
confidence: 99%
“…2 Around the same time, low-fat diets were widely promoted to prevent coronary heart disease (CHD), although this was found to be ineffective 50 years later. 3,4 In response to these recommendations, consumers increased consumption of dietary carbohydrates, particularly sugars, which were later found to increase serum lipids, a major risk factor for CHD. To further support this preliminary evidence, a large meta-analysis of prospective studies including 173,753 participants found that sugars in the form of sugar-sweetened beverages (SSBs) were associated with greater risk for CHD, with a 16% relative risk (RR) increase of CHD for each additional daily serving.…”
mentioning
confidence: 99%